Potensi Aktivitas Antibakteri dan Antioksidan dari Senyawa Bioaktif Bakteri Tanah Asal Samarinda, Kalimantan Timur: The Antibacterial and Antioxidant Potential of Bioactive Metabolites from Soil-Derived Bacteria in Samarinda, East Kalimantan - Atwita, Syelziva Yonda; Malau, Jekmal; Permatasari, Vera; Primahana, Gian; Dewijanti, Indah D.; Yuswan, Apriza; Prastya, Muhammad Eka (Jurnal Sumberdaya Hayati, 2025)
Antibiotic resistance is a global challenge, especially in the treatment of bacterial infections. This study aims to explore the antibacterial and antioxidant potential of bioactive compounds isolated from soil bacteria in Samarinda, East Kalimantan. Of the 30 isolates tested, 1 potential isolate was obtained, namely isolate code T1.16. This potential bacterial isolate was further cultured and fermented in Tryptic Soybean and Luria Bertani Broth medium to obtain its crude secondary metabolite. Interestingly, its crude extract showed antibacterial activity with MIC values of 100.4-3,211 µg/ml against Escherichia coli strain ATCC 8739, Pseudomonas aeruginosa strain ATCC 9027, Bacillus subtilis strain ATCC 6633, and Staphylococcus aureus strain ATCC 25923. Based on 1,1-diphenyl-2-picrylhydrazyl (DPPH) method was used to identify antioxidant activity, IC50 values obtained ranged from 990-1730 µg/ml. Ultimately, by using Gas Chromatography Mass Spectrometry (GC-MS) analysis, bioactive compounds in the form of Cyclo(L-prolyl-L-valine), 2-methylpropyl and phenylmethyl in bacterial extract T1.16 have potential antioxidant and antibacterial bioactivities. These results support the potential development of new antibacterial and antioxidant compounds from soil bacteria, as well as the importance of further exploration for pharmacological applications.